The role of accounting information systems in enhancing financial reporting quality of msmes: A systematic literature review - Padriyansyah Padriyansyah; Trie Sartika Pratiwi (Jurnal Mantik, 2026)
The advancement of digitalization has encouraged the adoption of Accounting Information Systems in the Micro, Small, and Medium Enterprises (MSMEs) sector; however, their effectiveness in improving the quality of financial statements has produced mixed results. This study aims to analyze and synthesize empirical findings on the role of accounting information systems in enhancing the financial reporting quality of MSMEs using a Systematic Literature Review (SLR) approach. The SLR method was implemented in accordance with the PRISMA protocol through four selection stages: identification, screening, eligibility assessment, and inclusion. The literature search was conducted across Google Scholar using keywords related to accounting information systems, financial reporting quality, and cloud accounting, covering publications from 2019 to 2025. Of the identified articles, ten (10) articles met the inclusion criteria and were analyzed through structured data extraction and thematic analysis. The synthesized findings indicate that Accounting Information Systems significantly enhance the financial reporting quality of MSMEs, particularly by improving reporting accuracy and timeliness. Their effectiveness is strongly influenced by user literacy and digital technology support, such as cloud-based and mobile accounting systems. This study contributes theoretically by mapping the key determinants of accounting information systems effectiveness and provides practical implications for application developers and policymakers in optimizing the utilization of accounting information systems among MSMEs